The role of ubiquitin-conjugating enzyme in the process of spermatogenesis - Peng Lv; Jihong Liu; Xiaming Liu (BMC, 2024)
Abstract The ubiquitination is crucial for controlling cellular homeostasis and protein modification, in which ubiquitin-conjugating enzyme (E2) acts as the central player in the ubiquitination system. Ubiquitin-conjugating enzymes, which have special domains that catalyse substrates, have sequence discrepancies and modulate various pathophysiological processes in different cells of multiple organisms. E2s take part in the mitosis of primordial germ cells, meiosis of spermatocytes and the formation of mature haploid spermatids to maintain normal male fertility. In this review, we summarize the various types of E2s and their functions during distinct stages of spermatogenesis.